2014
DOI: 10.1111/jonm.12268
|View full text |Cite
|
Sign up to set email alerts
|

Influence of work values and personality traits on intent to stay among nurses at various types of hospital in Taiwan

Abstract: The study findings provide evidence for managers to develop an optimal strategy for nurses with specific personality traits and highly positive work values, which can guide the recruitment and retention of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…In China, influenced by traditional concepts, nurses do not have a high sense of value. Chen 18 pointed that the more value the nursing work has, the stronger the intention to stay. Similar results were also found in Japan.…”
Section: Professional Social Statusmentioning
confidence: 99%
“…In China, influenced by traditional concepts, nurses do not have a high sense of value. Chen 18 pointed that the more value the nursing work has, the stronger the intention to stay. Similar results were also found in Japan.…”
Section: Professional Social Statusmentioning
confidence: 99%
“…This study considered additional variables, including the health status and type of work shift and hospital and examined their relationships with ITS (Sourdif , Letvak & Buck , Chen et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies indicated age, gender, education level and health status were associated with nurses' turnover intention (Burmeister et al., 2019; Jiang et al., 2019; Liu et al., 2012). The relationship between nurses' personality traits and their turnover intention has also been investigated (Chen et al., 2016). A proactive personality (Zampetakis, 2008) refers to an individual having a stable character with proactive behaviour, which allows opportunities to be identified and action to be taken to affect circumstances.…”
Section: Introductionmentioning
confidence: 99%